2018
DOI: 10.1111/ijcs.12493
|View full text |Cite
|
Sign up to set email alerts
|

Clean laundry with pure conscience—A study on laundry practices among Finnish consumers

Abstract: The previous study concerning laundry practices in Finland was published 16 years ago. Since that time, many pro‐environmental debates have been going on and sustainable actions have been implemented in many areas of individual lives and households. The purpose of this study is to investigate the textile laundering practices of Finnish consumers and their attitudes toward clothing care procedures. This study discusses how laundry habits could be developed into a more sustainable direction. The data for this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(45 citation statements)
references
References 19 publications
0
45
0
Order By: Relevance
“…The challenge for wearable textiles is wet washing, which is most favoured by consumers . In particular, cellulose fibres are challenging in terms of washing because the attachment of biocolorants to the fabric is weak, and the stability of the chemical structure against the pH change in washing liquid causes, in most cases, a change in the observed colour.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The challenge for wearable textiles is wet washing, which is most favoured by consumers . In particular, cellulose fibres are challenging in terms of washing because the attachment of biocolorants to the fabric is weak, and the stability of the chemical structure against the pH change in washing liquid causes, in most cases, a change in the observed colour.…”
Section: Resultsmentioning
confidence: 99%
“…According to these results, a new mindset could be useful in textile care procedures, about how textiles are used and maintained. Studies show that textiles are washed in extensive cycles and that excessive amounts of detergents are used [32,35,36], in many cases without the textiles being particularly dirty. Our study showed that people carefully follow the textile producers' care labels [32] and that therefore, from the perspective of biocolorants, it is Table 4 Colour fastness to light (LF) and washing fastness to domestic and commercial laundering (WF) of dyed and printed materials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the information stickiness (i.e., label information that participants spontaneously remembered and reported afterwards), the most often recalled pieces of information were dosage instructions (27.8% of respondents) and washing instructions (18.6% of respondents). According to a recent Finnish study, the most used course of action to determine the detergent dosage is to follow the dosage instructions mentioned on the package (Miilunpalo & Räisänen, 2019). As the package is thus often consulted for this information (certainly the first time they use the brand), it is not surprising that this is also the information that sticks best.…”
Section: Information Recallmentioning
confidence: 99%
“…It is worth noting that shared laundries are common in many countries, especially in more densely populated areas. For example, shared laundries (e.g., communal laundry rooms within a multi-family building, or a commercial coinoperated facility) are often used in the Philippines (Retamal and Schandl 2018), Japan and Thailand (Moon 2020) and Finland (Miilunpalo and Raisanen 2019). A recent study by Laitala et al (2020) also found that the use of shared washing machines varied between 6 and 13% among consumers in China, Germany, Japan, UK, and the USA.…”
Section: Introductionmentioning
confidence: 99%